Formulating a Blue Ocean Strategy in the Banking Services Industry: Enhancing Customer Satisfaction through Improved Demand Fulfillment and Presenting an Optimal Pattern - Manuchehr Ghanbari; Ali Sabzali Yameqani; Yousef Rabbani; Kobra Sabzali Yamaqani (‫مدیریت بازرگانی)
Objective The competition level among banks and financial institutions in Iran is notably intense. Success demands a novel approach to differentiate itself from competitors and effectively address the current challenges posed by competition. This study aims to formulate a Blue Ocean Strategy model in the banking industry for enhanced customer demand fulfillment, employing a strategy canvas and a four-action framework. Additionally, it endeavors to achieve an optimal pattern through the utilization of optimization techniques.